Effect of Storage Temperature on Carotenoid and Vitamin C Content in Red Grapefruit - Lado, Joanna; Pascual, Marta; Zacarías, Lorenzo; Rodrigo, María Jesús (Agrociencia Uruguay, 2015)
Carotenoids and vitamin C are important attributes that contribute to the organoleptic and nutritional quality in citrus fruits. The fruits of red grapefruit owe their colouration to the presence of lycopene, a red linear carotene, both in the peel and the pulp, a very unusual feature in citrus fruits. This property confers relevant nutritional interest due to its powerful antioxidant activity and possible health benefits of the fruit. Postharvest refrigerated storage is a common practice in citrus fruits. In this study, we evaluated the effect of storage temperature on carotenoids and vitamin C content in the pulp and the peel of red Star Ruby (SR) grapefruit. Results indicate that the fruit stored up to eight weeks at 12 °C reach concentrations of total carotenoids in the peel three to four times higher than fruits kept at 2 °C. The higher storage temperature (12 ºC) favored the accumulation of linear carotenes (phytoene, phytofluene and lycopene) while decreased the level of carotenoids derived from lycopene (β-carotene and xanthophylls). Similarly, vitamin C content slightly increased in the peel of fruits stored at 12 ºC. However, no changes in carotenoid and vitamin C contents occurred in the pulp due to postharvest temperature.